Impact of physical activity on preeclampsia and angiogenic markers in the Finnish Genetics of Pre-eclampsia Consortium (FINNPEC) cohort - Noora Jaatinen; Eeva Ekholm; FINNPEC, Hannele Laivuori; Tiina Jääskeläinen (Annals of Medicine, 2024)
AbstractIntroduction Effect of physical activity in pregnancy on preeclampsia (PE) and angiogenic markers is not well understood. We studied the association of physical activity and PE in a case-control setting and assessed whether exercise in PE and non-PE women associate with maternal serum concentrations of soluble fms-like tyrosine kinase 1 (s-Flt-1), placental growth factor (PlGF) and soluble endoglin (sEng) and sFlt-1/PlGF ratio in the Finnish Genetics of Pre-eclampsia Consortium (FINNPEC) cohort.Materials and methods Participants completed a questionnaire on their background information and serum samples were collected from a subset. Questionnaire data on physical activity were available from 708 PE women and 724 non-PE women. Both first trimester serum samples and questionnaire data on physical activity were available from 160 PE women and 160 non-PE women, and second/third trimester serum samples and questionnaire data on physical activity were available from 139 PE women and 47 non-PE women. The PE and non-PE women were divided into categories of physically active (exercise 2 − 3 times/week or more) and physically inactive (exercise less than 2 − 3 times/week).Results A total of 43.4% of the PE women and 42.4% of the non-PE women were categorized as physically active. There were no differences in physical activity and exercise habits between the groups. The physically active women were more often nulliparous and non-smokers and had a lower body mass index. There were no differences in the concentrations of angiogenic markers (sFlt-1, PlGF and sEng and sFlt-1/PlGF ratio) between the groups who exercised more or less than 2 − 3 times/week.Conclusions In the FINNPEC study cohort, there was no association between physical activity and PE and no associations of physical activity in pregnant women with and without PE with maternal serum concentrations of sFlt-1, PlGF and sEng and sFlt-1/PlGF ratio.